Healthy City Project: An application of data envelopment analysis - Park S; Yoon K; Lee M (Dove Medical Press, 2021)
Sewon Park,1,2 Kichan Yoon,3,* Munjae Lee4,5,* 1Research Institute for Future Medicine, Samsung Medical Center, Seoul, 06351, South Korea; 2Department of Medical Device Management and Research, SAIHST, Sungkyunkwan University, Seoul, 06351, South Korea; 3School of Health Policy & Management, Health Science College, Korea University, Seoul, South Korea; 4Department of Medical Humanities and Social Medicine, Ajou University School of Medicine, Suwon, South Korea; 5Medical Research Collaborating Center, Ajou Research Institute for Innovative Medicine, Ajou University Medical Center, Suwon, South Korea*These authors contributed equally to this workCorrespondence: Munjae LeeAjou University School of Medicine, 206, World Cup-ro, Yeongtong-gu, Suwon, Gyeonggi-do, South KoreaEmail emunjae@ajou.ac.krPurpose: The importance of Korea's Healthy City Project has recently increased due to the growth of the elderly population and chronic diseases. Consequently, local governments are expanding the project to manage health at the local level; however, because local government resources are limited, efficient business operation is required. Thus, the purpose of this study is to present a plan for effective project management by developing a strategy for a Healthy City Project that is suitable for the scale of local governments.Methods: For efficiency analysis, data were collected from the homepages of 90 local governments that are implementing the Healthy City Project in Korea, and data envelopment analysis (DEA) was conducted using both the CCR model and the BCC model. The input variables for the DEA included budget, manpower, organization, planned projects, and research education. In addition, we selected program, network, and project performance as output variables.Results: Analysis results indicated that the CCR model identified 22 (out of 90) municipalities in which Healthy City Projects are implemented efficiently, while 68 are inefficient. The BCC model identified many more efficient regions than the CCR model; however, the difference was insignificant. Thus, the budget, manpower, planned projects, and network must be increased to improve efficiency.Conclusion: First, to improve the efficiency of the Healthy City Project, a sufficient budget must be secured during its implementation. Second, long- and short-term plans are needed to expand the Healthy City Program. Third, networks must be created for local governments to benchmark Healthy City Projects.Keywords: Healthy City Project, health policy, healthy city network, efficiency, DEA